Information visualization in 2016: concepts, content and technology - Pérez-Montoro, Mario (Anuario ThinkEPI, 2017)
Information visualization covers the basic functions of data storage and communication, and reasoning support; most of the recently developed visualizations include these functions. However, among these, a small subset stands out for their innovative approaches and contribution to the development of the discipline. This article will review some of the innovative visualizations developed in 2016 and organize them into three groups. On the one hand, we present a small selection of visualizations that incorporate conceptual novelties and new visual proposals. On the other hand, we show some others that have drawn attention to the importance of the data set they have visualized. Finally, we account for some of the technological advances that have been developed within the discipline throughout this year.
Keywords: Information visualization; 2016; Trends; Data visualization; Interactive visualization; Infographics; Multimedia visualization; Concepts; Contents; Technology.